Extremely slow nova VI548 Aql - Primak, N.; Pavlenko, E. P. (Одеські астрономічні публікації, 2017)
The results of VRI CCD photomet-rical observations of extremely slow nova V1548 Aql (Nova Aql 2001) in Crimean Astrophysical Observatory during 2001 - 2003 years are presented. During the outburst decline in 2001 there were quasi-periodic brightness variations with period about 57 days (or 28 days). There were also color changes during decline. Brightness variations of V 1548 Aql during long periods, behaviour in color diagrams are presented.The behaviour of slow Nova Aquilae 2001=V 1548 Aql is like the behaviour of some slow novas, i.e. V 723 Gas, HR Del, DO Aql.